Hypothalamic-pituitary axis response to a 0.25-MG dexamethasone test in women with fibromyalgia - González-Vives, Sara; Díaz-Marsá, Marina; De la Vega, Irene; Palomares, Nerea; Vázquez, Susana; López-Villatoro, José Manuel; Palomo, Tomás; Carrasco, José Luis (Stress (Amsterdam, Netherlands), 2020)
Fibromyalgia has been reported as having some clinical overlap with both depression and emotionally-unstable disorders, although both types of disorders present different cortisol suppression response to dexamethasone. In this study we investigated the hypothalamic-pituitary-adrenal system (HPA) in the fibromyalgic syndrome (FMS) using a dexamethasone suppression test (DST) of 0.25 mg designed to specifically detect cortisol hypersuppression. We studied 59 women (20 patients and 39 healthy controls) to whom the DST was administered together with a battery of psychometric tests. In our results, patients with FMS had significant lower levels of basal cortisol pre- and post-DST compared with control subjects. However, cortisol suppression rate in patients after DST was not significantly different than in controls. As other syndromes like post-traumatic stress disorder or emotionally unstable personality disorders, also related with high incidence of severe trauma, FMS patients presented significant low basal cortisol. However, they did not have cortisol hypersuppression as is commonly found in the mentioned disorders. The relation of FMS with lifetime traumas and with emotional instability should be further investigated in order to improve psychological treatment approaches for these patients.LAY SUMMARYPatients with fibromyalgic syndrome have basal hypocortisoism but no cortisol hypersuppression after dexamethasone infusion compared to control subjects, as other trauma-related syndromes.